Pembelajaran IPS Dalam Kurikulum 2013 - Adisel, Adisel; Afenti, Zinda Ziarzi; Natalya, Lindya; Melansari, Okta (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to understand social studies learning in the context of the 2013 curriculum, using a literature study research method where the research collects materials and data from books and journals. Thus the researcher can use all the information and thoughts that are relevant to his readers. The results of the study, the existence of social studies learning in the 2013 curriculum can increase the potential of students, especially in the ability of Soft skills and Hard skills. The 2013 curriculum in the formation of the system provides a learning experience for students, thus students have the opportunity to master the skills needed in the future. In conclusion, the 2013 curriculum in its role is able to change the learning system that is only centered on educators to be centered on the role of students who are given learning. The development of the 2013 curriculum is a reference for the social studies learning system. With the reasoning system owned by the social studies system, the 2013 curriculum learning system can be very effective, especially now that learning takes place using the Course Review Horay method, with this method it can lead to deeper student curiosity about the social studies learning system. Keywords: 2013 Curriculum, Social Science Studies, Literature Studies